Anchoring Retro Spirou et Fantasio and Spin-off Albums. Issue 2 (1st September 2021) - Pellegrin, Annick
Abstract: Émile Bravo's Le Journal d'un ingénu inaugurated a growing trend of setting Spirou, Fantasio, and friends in WWII times. Bravo's acclaimed work was followed by the first instalment of a history of Spirou that also contributed to fuelling the interest in retro settings for new albums related to Spirou's universe. In this article I consider such retro albums as a whole and argue that WWII is only one of the many anchors used by authors to fill a gap in the publication history of Spirou, that as time passes, authors rely increasingly on Spirou's recovered history and on new content from retro Spirou albums to anchor their work, and that, ultimately, such works are more interested in Spirou itself rather than in history per se. 1